Penerapan Model Pembelajaran Index Card Match Untuk Meningkatkan Motivasi Belajar Siswa Pada Pembelajaran Sosiologi - Hallomoan Hallomoan; Nurlizawati Nurlizawati (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This study aims to apply the index card match learning model to increase students' motivation to learn sociology in class XI IPS 2 SMAN 1 Rao Utara. The results of this study will be helpful for teachers as a guide in implementing a simple and fun learning model for students. By looking at the purpose of this research, it can be seen that this type of research is classroom action research (CAR), where the data collection technique that the author does is through the observation sheet. The subjects of this study consisted of 22 students in class XI IPS 2. Then the resulting data will be analyzed with quantitative descriptive techniques so that the resulting data can be tested for validity. The indicator of the success of this research leads to the average percentage of students' motivation in classical sociology learning, which is at least 70%. The results showed an increase in students' motivation to learn sociology. The pre-cycle found students' learning motivation with an average score of 15.58%, then in the first cycle of 42.85%, and the second cycle of 72.72%. Thus, this learning model has succeeded in increasing students' motivation to learn sociology in class XI IPS 2 SMAN 1 Rao Utara.